Limited evidence for graft selection in pediatric ACL reconstruction: a narrative review - Gianni De Petrillo; Thierry Pauyo; Corinna C. Franklin; Ross S. Chafetz; Marie‐Lyne Nault; Louis‐Nicolas Veilleux (Journal of Experimental Orthopaedics)
Abstract Anterior cruciate ligament reconstruction is the preferred treatment to anterior cruciate ligament injury. With the increase in anterior cruciate ligament injuries in both adults and skeletally immature patients comes the need for individualized anterior cruciate ligament reconstruction graft selection whether it is the type of graft (auto vs. allograft) or the harvesting site (hamstrings, iliotibial band, quadriceps, patella). Several factors need to be considered preoperatively in order to optimize the patients’ recovery and restore anterior cruciate ligament strength and function. These include age and bone maturity, preoperative knee flexor/extensor strength, sport participation, patient’s needs and anatomical characteristics. This paper aims at bringing evidence supporting the use of a personalized approach in graft selection for faster and more efficient return to sport and propose a theoretical framework to support the approach.